Manajemen Atonia Uteri - Rafialdi Fatwaddin, Muhammad; Assauri, Sopyan; Nurul Milenia, Uni (Rifa'Institute, 2022)
Background: Uterine atony is one of the post-partum bleeding that can cause death in the mother. Uterine atony is an obstetric emergency and is one of the top five causes of maternal death. Post-partum/post-partum bleeding (PPH) is bleeding that occurs after delivery. Uterine atony is the 5th cause of maternal death. Method: The source search was carried out on the online portal of journal publications as many as 16 sources from MedScape, Google Scholar and the Nation Center for Biotechnology Information / NCBI with the keywords